Child-care and participation in the labor market for married women in mediterranean countries - Catia Nicodemo; Robert Waldmann (Institute for the Study of Labor (IZA), 2009)
Parents in the labor force have balance their work and home life, including the choice of the type of care to provide for their children while they work. In this paper we study the connection between the married women's labor force participation, child care arrangements and the time that husbands and wives spent to take care of children in Mediterranean countries. As more women now are in the labor force the interest in the use child care and housework of husband have grown. We use the new database from the EU-SILC (European Survey on Income and Living Conditions) in 2006 and data from the ECHP (European Community Household Panel)in 2001, because these two data-set give us different information about child care and housework. The traditional role of mothers in child care activities is highly valued by many families, especially in Southern European countries. The results show that while Mediterranean countries have advanced in the incorporation of women into the labor market, most of them still have to assume total responsibility for housework and the care of the children. Child care arrangements is an important instrument for women to enter in paid employment.
urn:nbn:de:101:1-2009021676
Keywords: J13; J21; C1; C3; 330; Unpaid work; child care arrangements; labor supply; Kinderbetreuung; Frauenerwerbstätigkeit; Arbeitsangebot; Hausarbeit; Familienökonomik; Mittelmeerraum; EU-Staaten